A bibliography of Research on Languages and Dialects of Sarawak - Norahim, Norazuna (Universiti Malaysia Sarawak, 2013)
This paper attempts to provide an overview of previous studies and on-going research on languages and dialects of Sarawak. The paper compiles existing literature and identifies gaps in research on the subject, and discusses UNIMAS role in the development of this body of knowledge. Relatively, Sarawak is a linguistically heterogeneous populated territory, with 44-45 Austronesian languages occupying 124.450 km2. Language and dialect boundaries in the territory can be indistinct. The dichotomy of some these languages, whether they are dialects of a language, or a language in its own right, has yet to be supported by further comparative studies. Published work on linguistic groupings may not always correspond to native speakers' perceptions of their languages. Ethnic category may not reflect the diversities of speech communities that it subsumes. As a result, ethnic categorisation and the languages they speak were misleadingly represented. This is one area of research that is critically in need of further research. Thus far, literature on Sarawak has not advanced much from the initial categorisation of language families by earlier studies (e.g. Hudson, 1970/0978; Blust, 1974/1977 Asmah, 1983). Postgraduate theses and dissertations on linguistic description of languages are on an increase. Nonetheless, long term projects in the language documentation have yet to be outlined. A major attempt at initial documentation of selected communities by Asmah Omar was carried out in 1983. Researches by Summer Institutes of Linguistics (SIL) have also contributed to the development of literature on documentation of these languages. Nonetheless, literature on language planning of indigenous languages remains unexplored. The lack of local linguists' involvement is partly the factor for the inadequacies (of literature on languages and dialects of Sarawak). In addition, concerted language planning is also lacking, which is evidence from the non-existence of a language faculty in the territory that addresses these issues.